Respuesta a la fertilización nitrogenada de las líneas promisorias de arroz ‘go - 00294’, ‘go - 00308’, ‘go - 00367’ y ‘go - 00412’, en condiciones de secano, en la zona de Babahoyo - Pisco Valero, Fabricio (2013)
On the grounds of Mr. Abilio Pisco Herrera, located on the campus of the future Babahoyo Canton Province of Los Rios, a trial was conducted on response to nitrogen fertilization four rice promising lines, in order to: a) Assess the agronomic behavior of genotypes, b) Selecting higher yielding genotype agronomic c) Identify the appropriate level of nitrogen in order to maximize grain yield, d) Determine the agronomic efficiency of each genotype, and e) Economic analysis of grain yield according to the production cost of the treatments. Promising lines were: 'GO - 00294', `GO - 00308 ',` GO - 00367' and 'GO - 00412' and varieties `Iniap 17 ' and ` S - FL - 09'. Nitrogen levels were 0,80 and 160 kg / ha. We used split-plot experimental design with three replications. Corresponded to the main plot nitrogen levels (treatment) and experimental genotypes as subplots (subtratamientos) experimental subplot consisted of 8 rows of 5 m in length distributed to 0.25 m, giving an area of 2.0 m X 5.0 m = 10 m2. The useful experimental subplot was 1.0 m X 5.0 m = 5 m2, eliminating two rows on either side by edge effects.